Postpartum Depression Levels in Women After the Application of Assisted Reproduction Techniques and Their Affecting Factors - Zehra Çerçer; İbrahim Ferhat Ürünsak; Evşen Nazik; Seda Karaçay Yıkar (Atatürk University, 2024)
Objective: This study was carried out to determine postpartum depression levels and their affecting factors in women who became women after the application of assisted reproductive techniques. Methods: The study is descriptive and cross-sectional and was conducted with mothers (n=93) who had babies as a result of treatment at the infertility clinic of Cukurova University Hospital. Research data were collected using the "Personal Information Form" and "Edinburgh Postpartum Depression Scale (EPDS)". In the analysis of the research data, descriptive statistics, independent samples t-test, Kruskall Wallis and Mann Whitney U test were employed.Results: The EPDS mean score of the women in the study was determined to be 18.22± 3.22 and 94.6% of them were at risk for postpartum depression. Statistically significant differences were found between the EPDS mean score of the mothers and the gender of the baby they want to have, experiencing anxiety, and sharing problems with their spouse (p0.05).Conclusion: It was determined that mothers who have a baby as a result of infertility treatment are at risk for postpartum depression. Although a healthy outcome of pregnancies obtained as a result of treatment is eagerly awaited by the mothers, it also poses a risk for postpartum infertile mothers.